Role of computed tomography in the evaluation of regional metastasis in well-differentiated thyroid cancer - Vaish, Richa; Mahajan, Abhishek; Sable, Nilesh; Dusane, Rohit; Deshmukh, Anuja; Bal, Munita; D’cruz, Anil K. (Frontiers in Radiology, 2023)
Background: Accurate neck staging is essential for appropriate surgery and avoiding undue morbidity in thyroid cancer. Ultrasonography (US) is the modality of choice for evaluation, which has limitations, particularly in the central compartment, that can be overcome by adding a computed tomography (CT). Methods: 314 nodal levels were analysed in 43 patients with CT, and US evaluations were done between Jan 2013- Nov 2015. Images were reviewed by two radiologists independently who were blinded to histopathological outcomes. Sensitivity, specificity, negative predictive value (NPV) positive predictive value (PPV) and accuracy of US, CT and US+CT were calculated using histology as the gold standard. Results: Overall sensitivity, specificity, PPV, and NPV for US, CT, and US+CT were 53.9%, 88.8%, 74.1% and 76.4%; 81.2%, 68.0%, 60.1% and 85.9%; 84.6%, 66.0%, 59.6% and 87.8% respectively. The overall accuracy of the US was 75.80%, the CT scan was 72.93%, and the US+CT scan was 72.93%. For lateral compartment, sensitivity, specificity, PPV, and NPV for the US, CT, and US+CT were 56.6%, 91.4%, 77.1% and 80.5%; 80.7%, 70.6%, 58.3% and 87.8%; 84.3%, 68.7%, 57.9% and 89.6% respectively. The accuracy of the US was 79.67%, the CT scan was 73.98%, and the US+CT scan was 73.98% for the lateral compartment. For central compartment were 47.1%, 76.5%, 66.7% and 59.1%; 82.4%, 55.9%, 65.1% and 76.0%; 85.3%, 52.9%, 64.4% and 78.3% respectively. The accuracy of the US was 61.76%, the CT scan was 69.12%, and the US+CT scan was 69.12% for the central compartment. Conclusions: CT has higher sensitivity in detecting nodal metastasis; however, its role is complementary to US due to low specificity.